If f(x) = (logcot x tanx) (logtan x cot x)-1 + tan-1 (4x / 4 - x2 ), then f`(2) is equal to????

f(x)=logcotxtanxlogtanxcotx-1 + tan-14x4-x2f(x)=   logtanxlogcotx   logcotxlogtanx + tan-12x21-x22

f(x)=logtanxlogcotx2 + 2tan-1x2


f '(x)=2logtanxlogcotx1logcotx.1tanx.sec2x + logtanx-1log(cotx)21cotx-cosec2x  +  211+x22.12 f '(x)=2logtanxlogcotxsec2xtanx logcotx +  logtanx cosec2xcotx log(cotx)2 + 44+x2


So,  f '(2)=2logtan2logcot2sec22tan2 logcot2 +  logtan2 cosec22cot2 log(cot2)2 + 44+22                   =2logtan2logcot2sec22tan2 logcot2 +  logtan2 cosec22cot2 log(cot2)2 +12

  • -6
What are you looking for?